Effects of iron and zinc fortified milk supplementation on working memory of underweight poor-urban school children: A randomized double blind controlled trial - Hari Wahyu Nugroho; Endang Dewi Lestari; Harsono Salimo; Mayasari Dewi; Zusta'in Noor Adhim; Leilani Lestarina (Indonesian Pediatric Society, 2010)
Background Undernutrition associated micronutrientdeficiencies in children are still prevalent in most developingcountries. Iron and zinc deficiencies are the most commonmicronutrient deficiency globally, which significantly contributedeficits in cognitive function. Fortification with iron and zinc hasproven successfully in reducing certain cognitive impairmentslike memory.Objective To determine the effects of milk fortified with iron andzinc on memory of underweight poor-urban schoolchildren.Methods A double blind randomized controlled trial wasconducted on 218 underweight poor-urban schoolchildren aged7-9 years old; 113 children were supplemented twice daily with27 gram of milk fortified with iron pyrophosphate (12.15 mg) andzinc sulfate (4.4 mg) for three months, 105 children served ascontrols. Anthropometry measured including bodyweight, height,sitting height and middle upper arm circumference. Memory wasmeasured using digit span backward test in Wechsler IntelligenceScales III. Statistical analyses were performed with SPSS forWindows, version 11.0.Results Baseline data of digit span backward score in iron andzinc group was 2.4 (SD 1.2), and control group was 3.0 (SD 1.8).After intervention, mean digit span backward score in iron andzinc group was 3 .1 (SD 1.2) and in control group 3.0 (SD 1.3).There was no improvement digit span backward score in controlgroup after intervention, compared with 0.7 point improvementin iron and zinc group (P=0.009).Conclusion Milk fortified with iron and zinc improves workingmemory of underweight poor-urban schoolchildren.